(untitled) (Eurasian Journal of Philology Science and Education, 2016)
«Abbas-Gulgaz» is one of the typical love dastans. Although many versions and variants of this epic edition, specially investigated. There are three versions of the epic. One of them is a love story and epic compositions includes traditional features. Those who have gained a larger version of the nine-volume version. This version is mainly present in the territory of Armenia (Sevan, Aibaba, Lori-Pembek), Georgia (Region), Ganja, Tovuz-Gazakh region and South Azerbaijan (Garadagh-Tabriz, Urmia) environment typical minstrel. The second version of the story is small in size, the plot line, the motive is different from the composition and poetry.This version was published only one option. In this way, the third version, which differs according to the characteristic of Shirvan region. It was published in two versions. The course of events, characters, poetry is reflected in the different versions, each version. To understand the essence of the epic saga about Abbas and his version of the study is of particular importance differences options. Therefore, this article focuses on differences in versions of the epic version and directed and produced the epic out of view.